Guinness world records 2017 (Guinness World Records Limited, 2016)
The world's biggest-selling annual is back and bursting with thousands of amazing new records! Last year, our diamond anniversary edition was the Christmas #1. This year, we're building on this success to bring you an all-new design, thousands of exciting new and fully updated records, and exciting new photography from around the world. The 2016 edition is our most ambitious yet!